Dynamic Changes in the Expression of Interferon-Stimulated Genes in Joints of SPF Chickens Infected With Avian Reovirus - Wang, Sheng; Xie, Liji; Xie, Zhixun; Wan, Lijun; Huang, Jiaoling; Deng, Xianwen; Xie, Zhi qin; Luo, Sisi; Zeng, Tingting; Zhang, Yanfang; Zhang, Minxiu; Zhou, Lei (Frontiers in Veterinary Science, 2021)
Avian reovirus (ARV) can induce many diseases as well as immunosuppression in chickens, severely endangering the poultry industry. Interferons (IFNs) play an antiviral role by inducing the expression of interferon-stimulated genes (ISGs). The effect of ARV infection on the expression of host ISGs is unclear. Specific-pathogen-free (SPF) chickens were infected with ARV strain S1133 in this study, and real-time fluorescence quantitative PCR was used to detect changes in the dynamic expression of IFNs and common ISGs in joints of SPF chickens. The results showed that the transcription levels of IFN-α, IFN-β, and several ISGs, including myxovirus resistance (Mx), interferon-induced transmembrane protein 3 (IFITM3), protein kinase R (PKR), oligoadenylate synthase (OAS), interferon-induced protein with tetratricopeptide repeats 5 (IFIT5), interferon-stimulated gene 12 (ISG12), virus inhibitory protein (Viperin), interferon-alpha-inducible protein 6 (IFI6), and integrin-associated protein (CD47), were upregulated in joints on days 1-7 of infection (the levels of increase of Mx, IFIT5, OAS, Viperin, ISG12, and IFI6 were the most significant, at hundreds-fold). In addition, the expression levels of the ISGs encoding zinc finger protein 313 (ZFP313), and DNA damage–inducible transcript 4 (DDIT4) increased suddenly on the first or second day, then decreased to control levels. The ARV viral load in chicken joints rapidly increased after 1 day of virus challenge, and the viral load stayed high within 6 days of viral challenge. The ARV viral load sharply decreased starting on day 7. These results indicate that in SPF chicken joints, many ISGs have mRNA expression patterns that are basically consistent with the viral load in joints. IFN-α, IFN-β, and the ISGs Mx, IFITM3, PKR, OAS, IFIT5, ISG12, Viperin, IFI6, and CD47 play important roles in defending against ARV invasion, inhibiting ARV replication and proliferation, and promoting virus clearance. These results enrich our understanding of the innate immune response mechanisms of hosts against ARV infection and provide a theoretical basis for prevention and control of ARV infection.